Effect of growth regulators on in vitro multiplication of potato (Solanum tuberosum L.) cv. diamant (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Shoot tip and nodal segment explants from field grown plants were used as experimental materials in this investigation. All explants were cultured on MS medium supplemented with various plant growth regulators. For surface sterilization of explants, HgCl2 (0.1%) for 2 minutes was found to be most effective for complete killing of surface pathogens and getting healthy tissues. Shoot regeneration was observed from both shoot tips and nodal explants for the studied plant. Various concentrations of BAP (0.1, 0.2, 0.3mg/l) and GA3 (0.1, 0.2, 0.3mg/l) were used for shoot multiplication. In case of BAP, the highest length of shoot was recorded 4 cm and the highest percentage of shoot multiplication (73%) was noticed in MS+0.2mg/l BAP. And in case of GA3, the highest response for shoot multiplication (82%) was noticed in MS+ 0.1 mg/l GA3.But among all of the media formulations used in this experiment, the highest response for shoot multiplication (95%) within7-10 days was noticed in hormone free MS media. In case of root regeneration, the highest percentage (96%) of root induction was recorded in MS medium supplemented with no hormone.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 81-88